Police interviewing in Taiwan: A self-report survey of practices and beliefs - Wang, Fei (International journal of comparative and applied criminal justice, 2025)
Following upon a prior survey of 631 North American law enforcement officers, and in light of heightened concerns about false confessions, we assessed the interrogation practices and beliefs of 551 police investigators in Taiwan. Overall, participants estimated that they were 66% accurate at truth and lie detection, that 48% of suspects waived their rights, that they elicited self-incriminating statements from 75% of all suspects, and that 27% of suspects confessed in the presence of their attorney. Of particular note is the self-report by participants that 72% of their interrogation sessions were fully recorded. With regard to the use of various interrogation techniques, participants estimated that they often identified contradictions in the suspect’s story, confronted the suspect with actual evidence, appealed to the suspect’s self-interests, and isolated the suspect from family and friends. We discussed the consistency of our findings with prior research, addressed potential shortcomings, and made recommendations to future directions.